Development of methodological approach to the evaluation of mesoeconomic intellectual capital functioning - Журавльова, Ірина Вікторівна (Technology audit and production reserves, 2016)
Intellectual capital at the present stage has become the leading factor in the economy. Therefore, the value of managing this kind of capital is increased, which is possible only on the basis of evaluation system that theoretically based and suitable for practical use. However, despite the huge number of publications, the presence of institutional and theoretical premises still has not developed a unified methodological approach to the evaluation of both the intellectual capital and its functioning. The concept of its diagnosis just formed. Methodical maintenance requires its improvement in relation to the mesoeconomic level. In this study, under the intellectual capital is understood a system of interrelated competency, structural and customer capital. The concept of intellectual capital functioning is defined as a form of existence in the course of the circulation when performing both their functions – distribution, cost, capital formation, providing, investment, etc., and performing system-wide (external) economic functions of the system in which it is reproduced. The study was developed a methodical approach to the evaluation of mesoeconomic intellectual capital functioning. The system of indicators and tools is justified for evaluation of intellectual capital functioning of its circulation in stages: formation and use. The system of indicators is a multi-level and includes a summary measure of the intellectual capital of the region, integrated performance of its components – competency, consumer and structural capital and private indicators for each component. In addition, when evaluation of intellectual capital functioning, the dichotomy of «intellectual capital – regional economic system» is taken into account by determining the influence of both external factors on the formation of intellectual capital and the impact of the efficiency of the use of intellectual capital on the results of mesoeconomic system. Applied scientific scenario for evaluation of intellectual capital functioning was also developed.